2021
DOI: 10.1016/s2214-109x(21)00002-4
|View full text |Cite
|
Sign up to set email alerts
|

The Irie Classroom Toolbox, a universal violence-prevention teacher-training programme, in Jamaican preschools: a single-blind, cluster-randomised controlled trial

Abstract: Summary Background Violence is a leading global public health problem, and interventions in early childhood are important in the primary prevention of violence. We tested whether the Irie Classroom Toolbox, a violence-prevention teacher-training programme reduced violence against children by teachers and reduced class-wide child aggression in Jamaican preschools (catering to children aged 3–6 years). Methods We did a single-blind, cluster-randomised control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 24 publications
1
32
0
Order By: Relevance
“…The content of EmpaTeach has important similarities and differences to the rigorously trialled and effective Irie Classroom Toolbox [ 21 ] and Good School Toolkit [ 22 , 40 ] interventions to reduce teacher violence. Similar to these interventions, and as recommended by WHO’s school-based violence prevention guidance [ 41 ], EmpaTeach contains information on alternative discipline techniques and creates social support.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The content of EmpaTeach has important similarities and differences to the rigorously trialled and effective Irie Classroom Toolbox [ 21 ] and Good School Toolkit [ 22 , 40 ] interventions to reduce teacher violence. Similar to these interventions, and as recommended by WHO’s school-based violence prevention guidance [ 41 ], EmpaTeach contains information on alternative discipline techniques and creates social support.…”
Section: Discussionmentioning
confidence: 99%
“…WHO recommends school-based approaches to improve a range of child and adolescent health outcomes [ 17 , 18 ], but only a handful of evaluations of programmes to prevent violence from teachers to students have been conducted globally [ 19 , 20 ] and, to the best of our knowledge, none in humanitarian settings. Two interventions have been rigorously trialled, and both were proven effective in reducing violence from school staff to students [ 21 , 22 ]; however, both programmes were implemented in low-resource but stable contexts in Uganda and Jamaica. One is a whole-school approach focused on creating a conducive operational culture in schools and encouraging behaviour change for teachers, students, and school administration over 18 months [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, through the teacher-training program, preschool teachers were trained to provide a positive, structured classroom environment, with clear rules and expectations, and with behavioral supports to help children meet these expectations. These teacher behaviors promote the development of children's self-regulation skills, and in two recent Jamaican studies, we have found benefits to child self-regulatory competencies from training teachers in classroom behavior management (Baker-Henningham et al, 2019 , 2021 ). Self-regulation has been shown to predict longer-term gains to child outcomes in other studies (Bierman et al, 2008b ; Raver et al, 2011 ).…”
Section: Discussionmentioning
confidence: 82%
“…For instance, in Jamaica, the Irie Classroom Toolbox intervention has been recently evaluated in a cluster-randomized controlled trial in 76 preschools [ 44 ]. The intervention does not explicitly target teachers’ attitudes towards violence but aims to reduce violence against children by promoting teachers’ socio-emotional competence and equipping them with positive non-violent discipline techniques.…”
Section: Introductionmentioning
confidence: 99%